1997
DOI: 10.7326/0003-4819-126-8-199704150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Thiopurine S-Methyltransferase Deficiency: Genetic Basis for Azathioprine and Mercaptopurine Intolerance

Abstract: The major inactivating mutations at the human TPMT locus have been identified and can be reliably detected by PCR-based methods, which show an excellent concordance between genotype and phenotype. The detection of TPMT mutations provides a molecular diagnostic method for prospectively identifying TPMT-deficient and heterozygous patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
450
4
29

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 701 publications
(499 citation statements)
references
References 0 publications
16
450
4
29
Order By: Relevance
“…Unlike the original studies 13 which showed 100% concordance of TPMT genotype and phenotype, the current study shows concordance in only two of the seven patients with heterozygous genotype and intermediate TPMT activity, leading to AZA withdrawal or dose reduction because of cytopenia and megaloblastic anemia. Of the remaining five heterozygous AZA-treated patients, three had normal TPMT levels.…”
contrasting
confidence: 97%
“…Unlike the original studies 13 which showed 100% concordance of TPMT genotype and phenotype, the current study shows concordance in only two of the seven patients with heterozygous genotype and intermediate TPMT activity, leading to AZA withdrawal or dose reduction because of cytopenia and megaloblastic anemia. Of the remaining five heterozygous AZA-treated patients, three had normal TPMT levels.…”
contrasting
confidence: 97%
“…As might be anticipated, many techniques have been used to genotype TPMT, beginning with RFLP assays and later extending to allele-specific amplification, direct sequencing, SSCP, DHPLC and -more recently -use of a variety of high throughput platforms (Yates et al, 1997;Spire-Vayron de la Moureyre et al, 1998;Schaeffeler et al, 2003Schaeffeler et al, , 2004. However, beyond all of the usual issues associated with genotyping, TPMT pharmacogenetics serves to highlight -in a very practical sense -a limitation common to all of these genotyping methods, their inability to determine haplotype directly.…”
Section: Tpmt Genetic Polymorphism: Discovery and Clinical Significancementioning
confidence: 99%
“…[7,8]. В настоящее время известно более 20 полиморфных вариантов гена, при этом наибольшее клиническое значение у детей с гемобластозами придается следу-ющим генетическим аллелям: ТРМТ*3А, ТРМТ*3С, ТРМТ*2 [8][9][10][11]. Отмечается выраженная вариабель-ность встречаемости дефицита ТРМТ в зависимости от этнической принадлежности, в европейской попу-ляции частота выявления гетерозиготного носитель-ства аллелей составляет около 10 %, гомозиготного -около 1 % [8,10,12].…”
Section: Introductionunclassified